Health literacy and health behaviors of Guinean university students residing in Brazil - Andressa Suelly Saturnino de Oliveira; Florinda Francisco Adulai Seidi; Katarina Milly Pinheiro de Sousa; Gilvan Ferreira Felipe; Eliziê Pereira Pinheiro; Nila Larisse Silva de Albuquerque (Universidade Federal do Rio Grande do Sul, 2023)
ABSTRACT Objective: To evaluate the health literacy and health behaviors of Guinean university students residing in Brazil. Method: A cross-sectional, analytical study conducted with 51 Guinean university students residing in Brazil. A health behavior questionnaire and the Test of Functional Health Literacy in Adults - Short version were applied. Spearman correlation coefficient, U of Mann-Whitney and Kruskal-Wallis were calculated. Results: Health literacy was adequate (median=79; IQR=24). Reading comprehension (median=70; IQR=16) of health information was better than numerical comprehension (median=14; IQR=14). Better health literacy performance was found in those with daily screen time of 3 to 5 hours (p=0.004) and who consumed fatty meat (p=0.002). Conclusion: Adequate health literacy of Guinean university students was associated with mostly healthy behaviors, except for screen time and consumption of fatty meat.